THE CHALLENGES OF FAMILY BUSINESS SUCCESSION PROCESS: A CASE STUDY OF TWO MAJOR BATIK PERANAKAN ENTREPRENEURS IN PEKALONGAN AND SOLO - Lili Kristanti; Maureen Nuradhi (Faculty of Business, President University, 2021)
Family business has many challenges to sustain for generations. Two legendary Peranakan batik entrepreneurial families halted their businesses at the third generation and this research looks for the causes of this failure. Through qualitative research method, the conclusion drawn is that there is no mature succession planning from the predecessor to the successor. Meanwhile, the difference in motivation and commitment of the next generation of these two family businesses do not seem to cause a difference in the final journey of Batik Oey Soe Tjoen and Batik Tiga Negeri. Factors beyond succession planning and commitment of future generations can be subject to further research studies.